Respuesta :
(1 + cscx)/cosx+cotx = (1+cscx)/(cosx+cosx/sinx)
= (1+cscx)/cosx(1+1/sinx)
= (1+cscx)/cosx(1+cscx)
= 1/cosx
= secx
= (1+cscx)/cosx(1+1/sinx)
= (1+cscx)/cosx(1+cscx)
= 1/cosx
= secx
(1+cscx)/(cos x + cot x)
As cosec x is the inverse of sinx
csc x = 1/sinx,
and cotx is the ratio of cosx and sinx
cotx = cosx/sinx
(1+cscx)/(cos x + cot x)
(1 + 1/sinx) / (cosx + cosx/sinx)
BY taking LCM:
(sinx +1) / sinx* [ (sinxcosx + cosx) / sinx]
(sinx + 1) / (sinxcosx + cosx)
Taking cosx as common:
= (sinx + 1) / cosx*(sinx + 1)
= 1/ cosx is the answer
As cosec x is the inverse of sinx
csc x = 1/sinx,
and cotx is the ratio of cosx and sinx
cotx = cosx/sinx
(1+cscx)/(cos x + cot x)
(1 + 1/sinx) / (cosx + cosx/sinx)
BY taking LCM:
(sinx +1) / sinx* [ (sinxcosx + cosx) / sinx]
(sinx + 1) / (sinxcosx + cosx)
Taking cosx as common:
= (sinx + 1) / cosx*(sinx + 1)
= 1/ cosx is the answer